Pediatric prevention from the perspective of parents of children up to two years old - Agata Anna Salwa (Journal of Education, Health and Sport, 2018)
Background: During the first years of life, the child should be under the constant supervision of a specialist who will follow and supervise the proper development of the new organism. Systematic visits at the pediatrician will allow the doctor to see any developmental disorders, correct irregularities, carry out vaccinations in time, and help parents determine the principles of feeding and nursing the child, so as to strengthen his immunity. Each visit to the pediatrician should include a full medical examination, assessment of physical development (measurement of weight and height, as well as head circumference) and evaluation of psychomotor development.